KAJIAN AWAL PEMANFAATAN SAMPAH TERDEGRADASI SEBAGAI LAPISAN PENUTUP LANDFILL - Hadinata, Febrian (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2007)
The contradictive one on landfill for municipal solid waste is about cover system. For many landfills in Indonesia that commonly using controlled landfill system, where waste is filled into landfill and being covered by soil every few days. The covering with soil, especially for sanitation usage. The problem, the soil that used as a cover layer have a much bigger unit weight charasteristic than the unit weight of the waste itself. There is a stability problem here, evenly the unity between soil and waste, failure of cover layer, also the soil character that is so sensitive to water. The increasing of moisture content will so influence to the strength of the soil. As we know, in landfill, there is so much water come from wastes leachate, and also from precipitation. Degraded waste is one of the alternative material that can be use as a cover. The light unit weight and hidraulics character that like silt, are the advantage factors from degraded waste.